2017
DOI: 10.1103/physrevd.96.112005
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the shape of the Λb0Λc+μν¯

Abstract: The measured dependence of the differential decay rate upon the squared four-momentum transfer between the heavy baryons, q 2 , is compared with expectations from heavy-quark effective theory and from unquenched lattice QCD predictions. DOI: 10.1103/PhysRevD.96.112005 I. INTRODUCTIONIn the Standard Model (SM) of particle physics, quarks participate in a rich pattern of flavor-changing transitions. The relevant couplings form a complex 3 × 3 matrix, known as the Cabibbo-Kobayashi-Maskawa (CKM) matrix, chara… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 45 publications
3
63
0
Order By: Relevance
“…From the partial decay width Eq. (52), we first obtain the Λ b → Λ c µν µ normalised spectral distribution for the SM and compare it with the one measured by LHCb [70] in Figure 6. The green and yellow shaded areas indicate the estimated 10% and 20% errors in the prediction according to [64].…”
Section: λ B → λ C Lν Decaysmentioning
confidence: 99%
See 1 more Smart Citation
“…From the partial decay width Eq. (52), we first obtain the Λ b → Λ c µν µ normalised spectral distribution for the SM and compare it with the one measured by LHCb [70] in Figure 6. The green and yellow shaded areas indicate the estimated 10% and 20% errors in the prediction according to [64].…”
Section: λ B → λ C Lν Decaysmentioning
confidence: 99%
“…Once again, this figure serves to calibrate the performance of the CCQM form factors in this case. The points are the LHCb data [70] and the dashed black line, green and yellow areas mark the central CCQM results and a 10% and 20% deviation respectively.…”
Section: λ B → λ C Lν Decaysmentioning
confidence: 99%
“…Particularly there are rapid progresses in the study of Λ c decays at BESIII [22][23][24][25][26][27] and some recent studies on Λ b and Λ c decays by LHCb can be found in Refs. [28][29][30][31][32][33]. It is anticipated that many more decay modes will be established in future.…”
Section: Introductionmentioning
confidence: 99%
“…It would be interesting to examine this process in other decay processes such as as B → D ν and Λ b → Λ c ν. The each of these decays have analyses ( [11] and [12]) with available covariance matrices and partial branching fractions, although the volume of publicly data available is less than that of B → π ν, this methodology can be used to help rule out other parameterizations of the form factors for these decays.…”
Section: Discussionmentioning
confidence: 99%